Musical game-changers through history and how we listen with our eyes - Petropulos, Elizabeth-Hannah (Kansas State University, 2017)
This thesis will examine musical game changers in a chronological order. It will discuss how composers have redefined the face of their musical genre and comment on how the past of music affects the future of music. In addition, the following contents will make a case for the idea that individuals listen with their eyes. I will examine the effect that costumes and their design have on both the audience and the performers. The sixty minutes Masters Recital that is the basis of this thesis will consist works by the following composers and librettists: Christoph Willibald Gluck, George Bickwell, Theodore Kennick, William Schwenck Gilbert, Arthur Sullivan, Leoš Janáček, Jerome Kern, Oscar Hammerstein, Kurt Weill, Ira Gershwin, Moss Hart, Richard Rodgers, Oscar Hammerstein II, Benjamin Britten, Galt MacDermot, Gerome Ragni, James Rado, Stephen Sondheim, Marvin Hamlisch, Edward Kleban, Andrew Lloyd Webber, Catherine Johnson, Benny Anderssohn, Björn Ulvaeus, and Lin Manuel-Miranda. The recital will feature selections from Orfeo ed Euridice, The Black Crook, The Pirates of Penzance, Jenůfa, Show Boat, Lady in the Dark, Carousel, Peter Grimes, Hair, Company, A Chorus Line, Evita, Mamma Mia, and Hamilton: An American Musical. Each selection will be will be musically and dramatically analyzed as well as discussed from a costume design standpoint.
Keywords: Game-changers; Costume design; Musical; Theater